Gene expression and soluble protein level of PD-1 and its ligands (PD-L1 and PD-L2) in endometrial cancer. - Mohd Nazzary Mamat Yusof; Kah Teik Chew; Nirmala Chandralega Kampan; Abdul Muzhill Hannaan Abdul Hafizz; Mohamad Nasir Shafiee (PLoS ONE)
Checkpoint programmed death-1 (PD-1) and programmed cell death ligands (PD-Ls) are negative immunoregulatory molecules that assist tumour cells in evading the immune system. The interaction of PD-1 and PD-Ls inhibits T cells and tumour-infiltrating lymphocytes (TILs) while increasing the function of immunosuppressive regulatory T cells (Tregs). This leads to the evasion of the immune response by tumour cells. The roles of PD-1, PD-L1, and PD-L2 in endometrial cancer (EC) have not been fully elucidated. This study investigates the mRNA gene expression and soluble protein levels of these molecules in EC compared to controls, with detailed analysis of clinical profiles. The results showed that EC had significantly higher mRNA gene expression and soluble protein levels of PD-L1 and PD-L2, but not PD-1. Specifically, PD-1 mRNA gene expression was significantly higher in cases with less than 50% myometrial invasion. Additionally, the soluble protein level of PD-1 was substantially higher in patients under the age of 60. Higher gene expression of PD-L1 was observed only in advanced stages of EC. However, the soluble PD-L1 protein level was significantly elevated in type II EC, advanced stage, higher grade, lympho-vascular space invasion (LVSI), and in cases with myometrial invasion of 50% or more. PD-L2 mRNA gene expression and soluble protein levels significantly differed across all clinical profiles except for LVSI. These findings suggest that PD-1, PD-L1, and PD-L2 may serve as potential predictive biomarkers, which could be beneficial for the management of endometrial cancer patients through immunotherapy.